(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
A simple and precise stability indicating RP-HPLC method was developed and validated for simultaneous determination of Olmesartan Medoxomil (OLM) and Hydrochlorothiazide (HCTZ) in pure drug and Pharmaceutical marketed formulation. Chromatography was carried out on Inertsil ODS C18 (150 × 4.6 mm, 5m particle size) column in an isocratic mode with mobile phase containing 0.2 % acetate buffer and acetonitrile in the ratio of 60:40% v/v at a flow rate of 1.0 ml/min. The analyte was monitored using PDA detector at 252 nm. The retention time was found to be 5.080 min and 10.493 min for Hydrochlorothiazide (HCTZ) and Olmesartan Medoxomil (OLM) respectively. The proposed method was found to be having linearity in the concentration range of 20-120µg/ml for Olmesartan Medoxomil (OLM) and 12.5-75.0µg/ml for Hydrochlorothiazide (HCTZ) with correlation coefficient value of 0.999 respectively. The mean % recoveries obtained were found to be 99.86-100.02 % for Hydrochlorothiazide (HCTZ) and 99.92-100.16 % for Olmesartan Medoxomil (OLM) respectively. Stress testing which covered acid, base, peroxide, UV light, neutral and thermal degradation was performed on under test to prove the specificity of the method and the degradation was achieved. The developed method has been statistically validated according to ICH guide lines. Thus the proposed method can be successfully applied for the stability indicating simultaneous determination of Olmesartan Medoxomil (OLM) and Hydrochlorothiazide (HCTZ) in bulk and combined tablet dosage form and in routine quality control analysis.